(untitled) (Journal of the College of Basic Education, 2023)
Sleep is one of the basic needs for survival, just like food and water, and it is necessary for the growth of the organism and the continuity of its physical and mental activity, as evidenced by the disorders resulting from deprivation of it. The current research has two aspects, the first is theoretical by presenting the literature on clarifying the negative effects resulting from sleep disorders, and the second is applied, aiming to clarify the extent of the spread of each disorder as well as to identify the statistical significance between each disorder and the variables of sex and age as one of the most important variables affecting sleep disorders, and based on So, the sleep disorders scale was built and measured, and after processing the data statistically, the research assumptions were confirmed, on the basis of which a set of recommendations and proposals were developed.